Dogs : a history of our best friends - Judge, Lita (2023)
"Of all the animals on the planet, dogs have the widest range of roles in our daily lives. They're protectors, helpers, lifesavers-but most of all, they're family. And they've taken a fascinating journey to get to this point. Long ago, early wolves evolved from fierce predators into trusted partners. They became dogs! While we know dogs to be lovable and full of personality, they have also historically improved our lives in many practical ways, like guarding livestock to help humans form the first settlements, cleaning out infectious wounds, and finding food. Covering over 50,000 years of history, from cave-dwelling to the present day, Dogs chronicles both fascinating scientific details and the history of how dogs learned to live cooperatively alongside humans. Beautifully illustrated and thoroughly researched, award-winning author and illustrator Lita Judge explores how our lives are intertwined with dogs'-and that's what makes them our best friends"--
Includes bibliographical references.
Ages 4 to 8
Keywords: Dogs -- History -- Juvenile literature; Human-animal relationships -- History -- Juvenile literature